Predictive value of C-reactive protein levels for the early and later detection of postoperative complications after cytoreductive surgery and HIPEC - Roux, Alexia; David, Valentin; Bardet M, Sylvia; Auditeau, Emilie; Durand Fontanier, Sylvaine; Taibi, Abdelkader (Frontiers in Oncology, 2022)
Background Postoperative elevation of C-reactive protein (CRP) can be used in order to predict the postoperative complications in many indications. Cytoreduction surgery (CRS) associated with hyperthermic intraperitoneal chemotherapy (HIPEC) is associated with high morbidity. Objectives The aim of the study was to demonstrate the CRP predictive value for the occurrence of complications. Methods All patients who had CRS and HIPEC, regardless of the origin of peritoneal metastasis, were included in this retrospective study. Postoperative complications and CRP and white blood cell (WBC) counts were recorded from postoperative day (POD) 1 through 10. Results Among the 127 patients included, 58 (45.7%) had no complications (NCs), 53 (41.7%) had infective complications (ICs), and 16 (12.6%) had non infective complications (NICs). The IC group had a higher CRP value than the NC group, which was statistically significant from POD7 to POD10 (41.1 versus 107.5 p = 0.023 and 77.8 versus 140 p = 0.047, respectively). A cut-off CRP value was 169 mg/L at PODs 3-5 and 62 mg/L at PODs 7-10. The area under the curve (AUC) at POD5 was 0.56 versus 0.76 at POD7, p=0.007. The sensibility, specificity, positive and negative predictive values of these cut-offs were 55%, 83%, 74% and 67%, respectively. Moreover, 17 patients (32%) with ICs had a CRP value higher than these cut-offs before the diagnosis was made by the medical team. Conclusion This study suggested that postoperative complications could be predicted using the CRP cut-off value on PODs 3-5 (169 mg/l) and PODs 7-10 (62 mg/l) after CRS and HIPEC.